Customer Trust and the Intention to Use Digital Banking Services in the Era of Transformation - Surahman Surahman; Subur Harahap; Moh. Sholeh (Mandalika Institute, 2026)
This study examines the role of customer trust in influencing the intention to use digital banking services in the era of digital transformation. The research employs a qualitative library research approach by reviewing books, peer-reviewed journal articles, and other relevant scientific publications related to customer trust, digital banking, and behavioral intention. Data were analyzed using content analysis to identify recurring themes, conceptual relationships, and significant findings from previous studies. The results indicate that customer trust remains a fundamental determinant of digital banking usage intention despite continuous technological advancement. Trust reduces perceived risk and uncertainty while strengthening customers' confidence in the security, reliability, and integrity of digital banking services. Furthermore, the findings demonstrate that technological innovation alone is insufficient to encourage sustainable adoption without strong institutional credibility. This study contributes to the behavioral finance and digital banking literature by emphasizing trust as a strategic factor that supports long-term customer engagement and provides practical implications for financial institutions seeking to enhance digital banking adoption through trust-building strategies.